Monitoring of cross-country skiers by means of an expert model of potential performance - Pustovrh, J.; Cernohorski, B.; Jost, B. (Collegium Antropologicum, 2006)
On the basis of expert knowledge, an expert model of potential performance covering the motor, morphological, psychological, and sociological subspace was constructed (MMPS). The scores of variables were obtained by application of the computer program Sport Measurement Management System (SMMS). In the subjects included in measurements, trends of the obtained average scores of variables were established through various competition categories and age periods. The sample of subjects consisted of 48 cross-country skiers in three competition categories. Fluctuations in development in individual age periods are larger in the motor and morphological subspace. In the psychological subspace, an upward trend of average scores can be noticed, while the sociological subspace is not subjected to any essential changes in different age and competition categories. Monitoring of cross-country skiers across all three competition categories showed that in these age categories there are periods which owing to laws of development do not allow uniform progress. Therefore, the principle of individuality must be taken into account especially in planning the transformation process.